2015
DOI: 10.1002/mabi.201500058
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone‐Conjugated Polyamidoamine Dendrimer for Delivery of the Heme Oxygenase‐1 Gene into the Ischemic Brain

Abstract: Heme oxygenase-1 (HO-1) has anti-apoptotic and anti-inflammatory effects. In this study, the HO-1 gene was delivered into the brain using dexamethasone-conjugated polyamidoamine generation 2 (PAMAM G2-Dexa) for the treatment of ischemic stroke. PAMAM G2-Dexa formed stable complexes with plasmid DNA (pDNA). The pDNA delivery efficiency of PAMAM G2-Dexa was higher than that of polyethylenimine (PEI25k, 25 kDa), dexamethasone-conjugated PEI (PEI-Dexa), and PAMAM G2 in Neuro2A cells. Therapeutic effect of PAMAM G2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…In previous studies, PAMAM-Dexa and PEI-Dexa were shown to have an anti-inflammatory effect due to the dexamethasone moiety (17). The anti-inflammatory effect of dexamethasone is beneficial to decrease the inflammatory reaction in the ischemic brain (10).…”
Section: Characterization Of Pamam G2-dexamentioning
confidence: 97%
See 4 more Smart Citations
“…In previous studies, PAMAM-Dexa and PEI-Dexa were shown to have an anti-inflammatory effect due to the dexamethasone moiety (17). The anti-inflammatory effect of dexamethasone is beneficial to decrease the inflammatory reaction in the ischemic brain (10).…”
Section: Characterization Of Pamam G2-dexamentioning
confidence: 97%
“…Preparation of pDNA pβ-Luc, pSV-HO-1, and pEpo-SV-HO-1 were constructed previously (17,25). pEmpty was pSI, which was purchased from Promega (Madison, WI, USA).…”
Section: Synthesis Of Pamam-dexa and Pei-dexamentioning
confidence: 99%
See 3 more Smart Citations